Nursing students' perceived stress: Interaction with emotional intelligence and self‐leadership. Issue 4 (27th August 2021) - Yildirim‐Hamurcu, Sevda; Terzioglu, Fusun
Abstract: Purpose: The aim of the current study was to determine how emotional intelligence and self‐leadership levels could be related to perceived stress. Design and Methods: A total of 341 nursing students were enrolled in this descriptive correlational study. Study measures included a sociodemographic form, Emotional Intelligence Evaluation Scale, Revised Self‐Leadership Questionnaire, and Perceived Stress Scale for Nursing Students. Findings: Results showed that ''assignments and workload'' as well as "taking care of patients" were the highest sources of stress in clinical training. The emotional intelligence and self‐leadership levels had a significant negative correlation with the perceived stress. Practice Implications: Perceived stress affects students' academic and social success negatively. Therefore, it is important to develop students' emotional intelligence levels, self‐leadership perceptions.